Design, development, and evaluation of educational virtual reality environment: EVRECA - ÖZDENER DÖNMEZ, NESRİN (My University, 2023)
Numerous studies have been carried out in recent years on the use of virtual reality (VR) technologies and environments in education. On the other hand, many researchers have drawn attention to the inadequacy of studies that deal with the education process in virtual reality environments from a broad perspective. In this research, the process of designing, developing, and testing an educational virtual reality environment in the light of a design model that includes pedagogical, design, and technical steps have been experienced and reported with a holistic perspective. The study was carried out in a two meso cycle structure based on the educational design research methodology. In the scope of research, the educational virtual reality campus platform has been developed to provide a skill-based educational environment for learners. The Internet of Things training process in the platform was held in a single session with each participant. At the end of the practices, it has been seen that the training carried out on the platform can provide learning at both cognitive and skill levels; the knowledge learned in the virtual reality environment can be transferred to real life and has a lasting effect. Furthermore, it was determined that there was a reverse relationship between the participants’ sense of presence and their cognitive load, and there was a positive relationship between the participants’ sense of presence and their pleasure and arousal levels. It has been concluded that technical data such as frames per second, latency, draw call, and polygon count provided by the platform can have a remarkable effect on the VR experience.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Social Sciences and Humanities; Sociology; Education; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; EVRECA; FPS; Sense of presence; Skill-based learning; Virtual reality